Setting the Table : Ceramics, Dining, and Cultural Exchange in Andalucía and La Florida - Ness, Kathryn L. (Book collections on Project MUSE., 2017)
By exploring sites on both sides of the Atlantic and combining archaeological collections and documentary research, Ness considers how individuals in Jerez de la Frontera, Spain and in St. Augustine, Florida negotiated the political and cultural changes that followed the advent of the Bourbon dynasty and the extent to which these developments impacted their daily lives.